Development and Validation of Process for Resolution of Praziquantel Amine for Preparation of Chiral Praziquantel - Hu, Changyan; Wang, Dongling; Chen, Kunquan; Liu, Xu; Chen, Qichao; Sun*, Dequn (Asian Journal of Chemistry, 2014)
Investigation of the viability of scale up preparation for chiral praziquantel was included in WHO/TDR business plan. Resolution is the major strategy for preparation of single enantiomer. In this study, a stable and effective resolution approach toward the important intermediate praziquantel amine for preparation of chiral praziquantel was developed and the process was optimized to afford high ee value and good yield. The suitable HPLC method was validated for the determination of ee value of chiral praziquantel amine.